Pergeseran Konsep Pengelolaan Ziswaf Dalam Peraturan Perundang-Undangan Di Indonesia - Maylen Fitria (Institut Agama Islam Negeri Metro, 2019)
Abstract Shari'at regarding zakat, infaq, and sadaqah, is a shari'ah which shows that in Islam, not only is the relationship between humans and God important, but the relationship between humans and humans is important. In the context of legislation in Indonesia, there are two laws that deal with zakat, u 38/99 and 11/23, whose focus is the management of zakat. in both of these laws, there is no significant difference between the two rules except for the centralized management aspect of u 38 38999 and is centralized on u 23/2011. The orientation is still the same, which is to realize the hope that zakat can be one solution in realizing equity and economic justice. Keywords: zakat law, management of zakat, purpose of zakat.